Decision-making for supplier selection of supplement packaging - Yuliarty Popy; Manulang Dea Amelia; Dwiasnati Saruni; Hidayat Rahmat Rian (BIO Web of Conferences)
This research was conducted on manufacturers of various pharmaceutical products in Indonesia, especially multivitamins and over-the-counter medicines, and focused on packaging, which also plays a significant role. The company orders cardboard packaging from several suppliers. The problem is that there are still many cardboard packages with defects, such as stains on the information cover, faded writing, nonstandard colors, illegible barcodes, and torn cardboard, resulting in a manual sorting process which results in wasted working time and disrupts production schedules. This research aims to select potential suppliers to reduce this problem by implementing the AHP method to determine weights and the MOORA method to determine priority choices from existing alternative suppliers. The results of the research, using the AHP method, obtained criteria weights, namely quality of 38%, delivery of 24%, cost of 21%, responsiveness of 10%, and flexibility of 7%, with the MOORA method the ranking results were obtained, namely first place Alternative 1, second place Alternative 2, and the third rank is Alternative 3. This shows that Alternative 1 is a priority supplier that can be recommended as the best supplier.